1992
DOI: 10.1007/bf00596501
|View full text |Cite
|
Sign up to set email alerts
|

Supracerebellar arachnoid cyst and reversible tonsillar herniation: magnetic resonance imaging and pathophysiological considerations

Abstract: A large supracerebellar arachnoid cyst was associated with herniation of the cerebellar tonsils and deformity of the cervicomedullary junction in an adult. Magnetic resonance imaging showed partial restoration of normal anatomy following surgery and clinical improvement, which helped in the formulation of a etiopathogenetic hypotheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Arachnoid cysts are predominantly located in the sylvian fissure. [18,51,139] However, cysts in any other location, such as the anterior [7] and posterior cranial fossa, [31,58,78] quadrigeminal cistern, [49,100,127] interhemispheric fissure, [51] suprasellar region, [56,103] or intraventricular space, [72,83,138] are suitable for an endoscopic approach.…”
Section: Arachnoid Cystsmentioning
confidence: 99%
“…Arachnoid cysts are predominantly located in the sylvian fissure. [18,51,139] However, cysts in any other location, such as the anterior [7] and posterior cranial fossa, [31,58,78] quadrigeminal cistern, [49,100,127] interhemispheric fissure, [51] suprasellar region, [56,103] or intraventricular space, [72,83,138] are suitable for an endoscopic approach.…”
Section: Arachnoid Cystsmentioning
confidence: 99%
“…Cerebellar tonsil herniation can be a catastrophic outcome of mass effect in the cranium. Both supratentorial and infratentorial lesions can result in cerebellar tonsil herniation (Floris et al, 1992; Onesti et al, 1997; Sheehan & Jane Sr, 2000). We aimed to model and quantify the effect of a supratentorial mass on the position of the cerebellar tonsils in cadaveric specimens.…”
Section: Discussionmentioning
confidence: 99%
“…Using this model, for every 1 mmHg increase in ICP, the cerebellar tonsils descended by approximately 0.3 mm. can result in cerebellar tonsil herniation (Floris et al, 1992;Onesti et al, 1997;Sheehan & Jane Sr, 2000). We aimed to model and quantify the effect of a supratentorial mass on the position of the cerebellar tonsils in cadaveric specimens.…”
Section: Tonsillar Herniation With Icp Changes Following Balloon Infl...mentioning
confidence: 99%
“…However, there is evidence in the literature of this possibility. Floris et al reported a case of a patient in whom a supracerebellar cyst caused reversible tonsillar herniation [14].…”
Section: Discussionmentioning
confidence: 99%